Differential expression profile of microRNAs in human placentas from preeclamptic pregnancies vs normal pregnancies. - Zhu, X; Han, T; Sargent, I; Yin, G; Yao, Y (2009)
OBJECTIVE: The purpose of this study was to perform a comprehensive analysis of the microRNA expression profile in placentas from preeclamptic pregnancies vs normal placentas. STUDY DESIGN: Placentas were obtained from patients with (1) mild preeclampsia (n = 8) and (2) severe preeclampsia (n = 15) and (3) in a normal control group (n = 11) with elective cesarean delivery. The microRNA expression profile was assessed by microRNA microarray and real-time reverse transcriptase-polymerase chain reaction analysis. RESULTS: Thirty-four microRNAs were expressed differentially in preeclamptic placentas, compared with normal placentas. Of these, 11 microRNAs were overexpressed, and 23 microRNAs were underexpressed in preeclamptic pregnancies. Notably, several microRNA clusters on human chromosome 19q13.42, 13q31.3, Xq26.2, Xq26.3, and 14q32.31 (a human imprinted region) were expressed differentially in preeclamptic placentas. These results were confirmed with the use of real-time polymerase chain reaction for selected microRNAs (miR-210, -152, -411, and so on). CONCLUSION: The results show that 34 microRNAs are deregulated in preeclamptic pregnancies, which suggests the involvement of these microRNAs in the pathogenesis of preeclampsia.